Bifacial quasi-solid-state dye-sensitized solar cells with metal selenide counter electrodes. (10th January 2016) - Yang, Peizhi; Tang, Qunwei
Graphical abstract: Highlights: Metal selenides are deposited on Ti grid for CEs of DSSCs. The PAA-PEG gel electrolyte is optical semitransparent. The bifacial quasi-solid-state DSSC can generate electricity from either side Ti grid supported RuSe CE displays the maximum electrocatalytic activity. The front efficiency of 6.51% and rear efficiency of 1.84% are recorded in the DSSC. Abstract: Bifacial dye-sensitized solar cell (DSSC) is a promising solution to reduce the cost of photovoltaic conversion. We present here the experimental realization of bifacial quasi-solid-state DSSC from a TiO2 photoanode, a semitransparent gel electrolyte, and a Ti grid supported metal selenide (MSe, M = Co, Ni, Ru) counter electrode (CE). In comparison with front efficiency of 4.87% and rear efficiency of 1.19% for Ti grid supported Pt based DSSC, the efficiencies are enhanced to 6.51% and 1.84% on the solar cell with cost-effective Ti grid supported RuSe CE. The preliminary results demonstrate that this architecture is promising in realizing cost-effective bifacial quasi-solid-state DSSCs without sacrificing photovoltaic performances.